Feasibility Study of the Development of Ground-Mounted Solar Plants - Ekacitta, Puti Cresti; Iyi, Draco (Indonesian Journal of Energy, 2025)
Indonesia is building a new capital city in Penajam Paser Regency. The government aims to maximise the utilisation of low-carbon energy in the new capital. With a favourable location at the equator crossing, Penajam Paser Regency has a Global Horizontal Irradiance (GHI) index higher than Indonesia's regional average—1,753 kWh/m²/year—and a solar potential of 13,749 MW. Therefore, solar energy in this location has the potential to meet the city's total energy demand. However, the regency currently has no ground-mounted solar energy projects. Our study examines the technical feasibility of implementing ground-mounted photovoltaic (PV) power plants in Indonesia's new capital city. It explores the technical and economic aspects of providing clean electricity and represents the first study of ground-mounted PV systems in the region. We compare the simulation results of Helioscope and PV Syst for designing a ground-mounted PV system. We then analysed economic feasibility by comparing two possible tariffs, which are the ceiling price and system generation cost. We reveal that the optimal PV system design has a 14.79 MWp capacity, producing 22.4 GWh of electricity annually. This system can be developed using a Power Purchase Agreement (PPA) plan over a 25-year operational duration. Economic analysis yields an Internal Rate of Return of 22.99%, a Net Present Value of GBP 6,083,060, a payback period of 8.4 years, and a Levelized Cost of Energy of GBP 0.056/kWh.